2007
DOI: 10.1182/blood-2006-09-048322
|View full text |Cite
|
Sign up to set email alerts
|

Gata1 regulates dendritic-cell development and survival

Abstract: IntroductionDendritic cells (DCs) are key initiators and regulators of the immune response. DCs were originally described by the exclusive capacity to stimulate naive T cells. 1 Later studies showed that DCs are also involved in the stimulation of regulatory responses through the propagation of regulatory T cells. 2 Two types of DCs have been defined in mice and humans based on differential surface marker expression, origin, or function in the immune response: myeloid DCs (mDCs) and plasmacytoid DCs (pDCs). 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 57 publications
6
68
0
1
Order By: Relevance
“…Importantly, we have also specifically shown the ability of the prototypic hemopoietic transcription factor GATA1 to regulate D6 expression and this is in keeping with the known importance of GATA1 for differentiation along many of the lineages we show here to be positive for D6 expression (32,33,41). Both primary human DCs and mouse bone marrow-derived DC cultures express high levels of D6.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Importantly, we have also specifically shown the ability of the prototypic hemopoietic transcription factor GATA1 to regulate D6 expression and this is in keeping with the known importance of GATA1 for differentiation along many of the lineages we show here to be positive for D6 expression (32,33,41). Both primary human DCs and mouse bone marrow-derived DC cultures express high levels of D6.…”
Section: Discussionsupporting
confidence: 54%
“…Notably, the promoters (as shown for the mouse and human promoters in Fig. 1C) were seen to contain binding sites for a variety of transcription factors associated with hemopoietic lineagespecific differentiation (32,33). These include Ikaros (suggestive of T cell and DC expression), Myb (megakaryocyte expression), and FIGURE 1.…”
Section: D6 Is Expressed By Leukocytes In Inflamed Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated that GATA1 is a physiological regulator of D6 expression [75] using mice with a conditional deletion in GATA1 [78]. In DC of these mice, the knockdown of GATA1 is associated with a transcriptional switch-off of D6 expression confirming a role for GATA1 in the regulation of D6 expression.…”
Section: Regulation Of D6 Expressionmentioning
confidence: 95%
“…The WBC counts were not significantly altered during the course of Tx treatment ( Figure 3C), although in a separate study we found that Gata1 loss affected differentiation and survival of eosinophils and dendritic cells. 2 To investigate whether the KO-Tx mice respond to the induced anemic condition, we measured Epo levels in plasma ( Figure 3D). In KO-Tx mice at week 3, these ranged from 200 to 1000 pg/mL, which was up to 5-fold higher than normal levels.…”
Section: Gata1 Deficiency In Adult Erythropoiesis 4379mentioning
confidence: 99%